2017
DOI: 10.5194/soil-3-31-2017
|View full text |Cite
|
Sign up to set email alerts
|

Thermal alteration of soil organic matter properties: a systematic study to infer response of Sierra Nevada climosequence soils to forest fires

Abstract: Abstract. Fire is a major driver of soil organic matter (SOM) dynamics, and contemporary global climate change is changing global fire regimes. We conducted laboratory heating experiments on soils from five locations across the western Sierra Nevada climosequence to investigate thermal alteration of SOM properties and determine temperature thresholds for major shifts in SOM properties. Topsoils (0 to 5 cm depth) were exposed to a range of temperatures that are expected during prescribed and wild fires (150, 25… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 64 publications
4
34
0
Order By: Relevance
“…In studies conducted two to three years following a fire in the Sierra Nevada, high-severity fires were reported to decrease total C stocks in organic horizons relative to unburned treatments (Maestrini et al 2017, Adkins et al 2019. During high-severity fires, increases in soil heating can also decrease mineral soil C concentrations (Almendros et al 2003, Araya et al 2017) and lead to low molecular weight DOM (Norwood et al 2013, Santos et al 2016 transported from soils to streams. Our results suggest that an increase in fire severity decreased C and N concentrations and molecular size of DOM over time under baseflow conditions, likely due to the thermal degradation of topsoil OM.…”
Section: The Interaction Between Fire Severity and Time Since Firementioning
confidence: 99%
See 1 more Smart Citation
“…In studies conducted two to three years following a fire in the Sierra Nevada, high-severity fires were reported to decrease total C stocks in organic horizons relative to unburned treatments (Maestrini et al 2017, Adkins et al 2019. During high-severity fires, increases in soil heating can also decrease mineral soil C concentrations (Almendros et al 2003, Araya et al 2017) and lead to low molecular weight DOM (Norwood et al 2013, Santos et al 2016 transported from soils to streams. Our results suggest that an increase in fire severity decreased C and N concentrations and molecular size of DOM over time under baseflow conditions, likely due to the thermal degradation of topsoil OM.…”
Section: The Interaction Between Fire Severity and Time Since Firementioning
confidence: 99%
“…Fires can alter the cycling, concentration, and chemical composition of OM in soil (Santín et al 2015, Araya et al 2016, Santos et al 2016, Araya et al 2017 and aquatic ecosystems (Jaffé et al 2013, Masiello and. The thermal degradation of soil organic C and biomass produces a heterogeneous mixture of organic residues that are collectively referred to as pyrogenic (fire-derived) C (PyC).…”
Section: Introductionmentioning
confidence: 99%
“…The MIR data indicate that both the control and 10-year post-fire plots showed an increase in peak heights in the -OH function group (3,700 cm −1 ) with depth and a decrease in the −CH (2,940 cm −1 ). The ester and phenol regions (1,159 and 995 cm −1 ) also showed a decrease in peak heights with depth into the soil profile in both the pre-and post-fire spectra based on DRIFT spectra designations of Araya et al (2017). The most important differences in the MIR spectra in the soils from the burned and control plots, for regions of interest to SOM composition, (Figure 9) were observed in the spectral regions representing asymmetric and symmetric C-H stretching vibrations in aliphatic compounds (2,924 and 2,850 cm −1 , respectively); C = C stretching vibrations of aromatic compounds (1,650 cm −1 ); N-H bending vibrations and C = N stretching vibrations in amides (1,575 cm −1 ); C-H bending (1,390, 1,405, and 1,470 cm −1 ) in aliphatic groups; C-O stretching and asymmetric stretching vibrations in carboxylic and phenolic groups (1,270 cm −1 ); and C-O symmetric vibrations in polysaccharides (1,080 and 1110 cm −1 ).…”
Section: Standard Error Presented In Parentheses (N = 30)mentioning
confidence: 99%
“…Spectra were background corrected against silicon carbide and then baseline corrected. Peak region assignments were adapted from Araya et al (2017).…”
Section: Spectroscopymentioning
confidence: 99%
“…Fires can lead to destabilization of topsoil, reducing aggregation and aggregate protected C, increased soil hydrophobicity, which can lead to increased erodibility of soil post-fires through both water and wind-driven erosion processes (Shakesby and Doerr, 2006;Johnson et al, 2007;Ravi et al, 2007;Al-Hamdan et al, 2012;Miller et al, 2012;Araya et al, 2017). Albalasmeh et al (2013), for example, showed that low severity fires can have a lasting impact on soil aggregate stability.…”
Section: Effect Of Fire and Pyc On Soil Erosionmentioning
confidence: 99%